PEMBELAJARAN BIOLOGI DENGAN MODEL POE (PREDICT-OBSERVE-EXPLAIN) MENGGUNAKAN MULTIMEDIA FLASH DAN VCD DITINJAU DARI KEMAMPUAN VERBAL DAN KREATIVITAS SISWA - Nawawi Nawawi; Sugiyarto Sugiyarto; Sutarno Sutarno (Magister Pendidikan Sains Universitas Sebelas Maret, 2013)
This study is intended to find the influence of the Multimedia Flash and VCD in the teaching and learning of plant movement that used POE learning model overviewed from verbal ability and student‘s creativity. The research took 2nd graders of SMP Nuris Semarang. The research took place in the beginning of the second semester of 2011/2012 academic year. There were two classes selected at Nuris junior high school as research groups. The research instruments were in the forms of lesson plan, teaching-learning materials, students activity sheets, observation sheets, tests. The influence of Multimedia Flash and VCD on the students‘ learning results and data’s were analysed by ANOVA with three way analysis of variances. The study showed that (1) there were no effect of the use of Multimedia Flash and VCD with POE learning model, (2) there were an effect of verbal ability on affective and psychomotor aspect, (3) there was no effect of creativity for achievement affective and psychomotor aspect, but there is an influence of cognitive aspect, (4) there was no interaction between Multimedia Flash and VCD with verbal ability on achievement affective and psychomotor aspect, but there is an interaction influence for cognitive aspect, (5) there was an interaction on creativity with Multimedia Flash and VCD from cognitive and affective aspect, (6) there were no interaction between verbal ability and creativity of students, (7) there were no interaction between Multimedia Flash and VCD, verbal ability and creativity for cognitive, affective and psychomotor. Keywords: Media Education, Verbal Ability, Creativity and Plants Movement